Falling into a deep dark hole: Tongan people's perceptions of being at risk of developing type 2 diabetes. (22nd May 2020) - Faletau, Julienne; Nosa, Vili; Dobson, Rosie; Heather, Maryann; McCool, Judith
Abstract: Background: Prediabetes is a precursor for type 2 diabetes. Compared to the New Zealand/European and other population groups (24.6%), the prevalence of prediabetes is higher within Pacific groups (29.8%). The diagnosis of prediabetes presents a potential opportunity to intervene to prevent progression to type 2 diabetes. Objective: To develop an understanding of how being 'at risk' of developing type 2 diabetes is perceived by Tongan people with prediabetes living in Auckland, New Zealand. Methods: The Kakala and Talanga Tongan methodologies underpinned this study. Twelve one‐on‐one, semi‐structured interviews with Tongan patients who had prediabetes from a primary health‐care clinic in Auckland, New Zealand, were conducted. Thematic analysis was used to identify recurrent themes from the data. Results: Participants were not aware of their prediabetes diagnosis, emotions associated with the diagnosis reflected fear and disbelief and a perception of imminent danger. Family history informed perceptions of the risk of developing type 2 diabetes. Participants could not differentiate prediabetes from type 2 diabetes, and recollections of being 'back in the Islands' of Tonga were consistent with healthy lifestyles. Conclusions: Prediabetes appeared to be poorly understood and was believed to be irreversible, which could discourage behaviour change, social and physical improvements in health. Appropriate culturally tailored messages to accompany a prediabetes diagnosis, including cause and management, would be beneficial for Pacific peoples.